History and economic life
1 online resource.
Keywords: "This book offers students a wide-ranging introduction to both quantitative and qualitative approaches to interpreting economic history sources from the Middle Ages to the Twentieth Century. Divided into two parts, it both equips students with a toolbox to approach economic history sources and includes case studies that examine how economic historians use such sources. Introducing sources often avoided in culturally-minded history or statistically minded economic history courses respectively and advocating a combined quantitative and qualitative approach, it is an essential resource for students undertaking source analysis within the field"--